Methods for assessing the impact of infectious diseases of livestock - their role in improving the control of Newcastle disease in Southern Africa - McDermott, John J.; Coleman, P.; Randolph, Thomas F. (Australian Centre for International Agricultural Research, 2001)
A framework for the impact assessment of disease control strategies for Newcastle disease (ND) is discussed. This includes linking epidemiological and economic data to predict the relative impact of different control interventions at different levels from farm to region. Epidemiological transmission models assume that village poultry are the reservoir of ND virus for other sectors. Simple models for transmission of the virus among village chickens predict that for vaccination to be effective, it must be conducted relatively frequently with a large proportion of chickens covered. Extrapolations to transmission between village and commercial sectors are suggested. Economic issues at farm level are considered most influential. Decisions to invest in national and regional projects will depend on the assessment of social equity impacts and cost-benefit and institutional analyses to assess relative benefits of private versus public sector interventions. Capturing the perspectives of all stakeholders in the ND control intervention process is considered crucial to both enhanced impact and sustainability of any control program.